Cases on Business Law with Notes and Problems (Book). - Hulvey, Chas. N. (The Accounting Review, 1936)
Reviews the book "Cases on Business Law With Notes and Problems," by Leslie J. Ayer and Paul P. Ashley and Stephen D. Brown.